88.3k views
5 votes
Solve the equations
x squared + y squared = 36
x = 2y + 6

User Francisco
by
5.2k points

1 Answer

4 votes

Answer:

Given the equations:


x^2+y^2 =36 .....[1]


x =2y +6 ....[2]

Substitute the value of x in [1] we get;'


(2y+6)^2+y^2 =36

Use identity:
(a+b)^2= a^2+2ab+b^2


4y^2+36+24y + y^2 =36

Combine like terms;


5y^2+36+24y=36

Subtract 36 from both sides we get;


5y^2+24y=0


y (5y+24) = 0

By zero product property, we get;

y = 0 and
y =- (24)/(5) = -4.8

Substitute these y values in [2] to get x values;

For y = 0 we have;

x = 2(0) +6 = 0+6 = 6

For x = -4.8

x = 2(-4.8)+6 = -9.6 + 6 = -3.6

Therefore, the solution for the given equations are; (6, 0) and (-3.6, -4.8)


Solve the equations x squared + y squared = 36 x = 2y + 6-example-1
User David Harvey
by
6.4k points